1999
DOI: 10.1021/cm990376f
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport in Cryptand and Crown Ether Lithium Salt Complexes

Abstract: Amorphous solid electrolytes were formed by the interaction of cryptands or crown ethers with a lithium salt, Li[CF3SO2N(CH2)3OCH3], when the cavity size of the macrocycle does not match the diameter of the lithium cation. With the exception of [Li⊂18-C-6][(CF3SO2)2N] (the mathematical symbol of inclusion, ⊂, is used to indicate Li+ included in 18-C-6), the complexes of Li[(CF3SO2)2N] with cryptand and crown ethers do not form amorphous electrolytes. Complexes of Li[CF3SO2N(CH2)3OCH3] and Li[(CF3SO2)2N] were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 41 publications
5
36
1
Order By: Relevance
“…3 shows the temperature dependence of ionic conductivity of the (12-Crown-4)-LiTFSI complexes at (1/1, 1/0.95 and 1/0.67 molar ratios). At temperatures below the second plastic transition, ∼89 • C, the 1/1 complex showed the highest conductivity throughout the plastic range reaching 4.6 × 10 −6 Scm −1 at 50 • C, a value close to the one reported by others [13]. The 1/0.95 complex showed lower conductivity than that of the 1/1 contradicting what we predicted that the availability of ion-free crown rings in the solid would provide a lower energy barrier for the Li ions to move from a complexed ring to an ion-free one.…”
Section: (18-crown-6)-litfsi Complexessupporting
confidence: 87%
“…3 shows the temperature dependence of ionic conductivity of the (12-Crown-4)-LiTFSI complexes at (1/1, 1/0.95 and 1/0.67 molar ratios). At temperatures below the second plastic transition, ∼89 • C, the 1/1 complex showed the highest conductivity throughout the plastic range reaching 4.6 × 10 −6 Scm −1 at 50 • C, a value close to the one reported by others [13]. The 1/0.95 complex showed lower conductivity than that of the 1/1 contradicting what we predicted that the availability of ion-free crown rings in the solid would provide a lower energy barrier for the Li ions to move from a complexed ring to an ion-free one.…”
Section: (18-crown-6)-litfsi Complexessupporting
confidence: 87%
“…In all the DSC curves, no peak due to the melting of pure glymes is observed (see Supporting Information (SI) Table S1), 10 suggesting that no free glyme molecules exist in the equimolar mixtures. It has been reported that the equimolar complexes of crown ethers (12-crown-4 (12C4) and 15-crown-5 (15C5)) and LiTFSA are solids at room temperature, 11 although 12C4 and 15C5 have the same number of oxygen atoms as G3 and G4, respectively. The glymes have higher conformational flexibility than the crown ethers, and the flexible structure of glymes may also give rise to conformational freedom in the molten complexes.…”
Section: ¹1mentioning
confidence: 99%
“…Cryptands can also be used as phase-transfer catalysts 8 and solid electrolytes 9 . In addition, they have been recently tested as fluorescent sensors for radioactive perthecnetate anions with very promising results 10 .…”
Section: Introductionmentioning
confidence: 99%